PERKEMBANGAN TEKNOLOGI SEL MAMALIA CHINESE HAMSTER OVARY (CHO) UNTUK PRODUKSI OBAT BERBASIS PROTEIN - Adi Santoso (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Chinese hamsters ovary (CHO) and its derivative such as CHO-DXB11 cells, CHO-K1, CHO-DG44 and CHO-S are mammalian cells that are often used for production of therapeutic protein drugs. The CHO cells often used for protein production have several advantages including 1) host cells that are safe to use in drug production, 2) the level of production of proteins produced can be increased by amplifying genes using methotrexate (MTX), 3) having the capacity to make post-translation modificationsand 4) CHO cells can be adapted to grow in suspension. The high need for protein-based drugs triggers the development of basic knowledge and innovation in production of recombinant proteins. The impressive technological advances in CHO cell technology have made these cells can be used to produce proteins around 10 g/liter in order to meet the market demand. The first protein successfully produced using CHO mammalian cells was the therapeutic Tissue Plasminogen Activator (r-tPA, Activase) protein used for stroke patients. The presence of this drug is quickly followed by several other types of drugs. In this review, history of development of CHO cells, the contribution of CHO cells to basic research, progress of effective line cell screening and development technology are discussed.